2021
DOI: 10.3389/fpsyt.2021.686514
|View full text |Cite
|
Sign up to set email alerts
|

Significant Increase in Depression in Women With Primary Dysmenorrhea: A Systematic Review and Cumulative Analysis

Abstract: Women with primary dysmenorrhea are vulnerable to develop a depressive disorder, which is a common form of psycho-disturbance. However, clinical findings are inconsistent across studies, and the evidence has not been previously synthesized. This study aims to investigate whether primary dysmenorrhea is associated with a higher risk of depression via a cumulative analysis. Four electronic databases were systematically searched for the eligible studies. The combined effect was assessed by analyzing the relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 48 publications
1
17
0
1
Order By: Relevance
“…However, the previous studies examining the association between dysmenorrhea and mental disorders showed inconsistent findings. Kabukçu et al [35], Westling et al [36], Zhao et al [37], and Gagua et al [38] have reported that dysmenorrhea severity is associated with a higher incidence of depression, anxiety, and stress disorders. Conversely, László et al [39] showed no significant correlations between dysmenorrhea and higher incidence of psychological disorders, whereas Namvar et al [40] reported that women with no dysmenorrhea exhibited higher anxiety symptoms than women with dysmenorrhea, and higher depression scores among women with dysmenorrhea than those without dysmenorrhea were reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, the previous studies examining the association between dysmenorrhea and mental disorders showed inconsistent findings. Kabukçu et al [35], Westling et al [36], Zhao et al [37], and Gagua et al [38] have reported that dysmenorrhea severity is associated with a higher incidence of depression, anxiety, and stress disorders. Conversely, László et al [39] showed no significant correlations between dysmenorrhea and higher incidence of psychological disorders, whereas Namvar et al [40] reported that women with no dysmenorrhea exhibited higher anxiety symptoms than women with dysmenorrhea, and higher depression scores among women with dysmenorrhea than those without dysmenorrhea were reported.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that oral contraceptives could manage menstrual pain by suppressing ovulation and endometrial ) is metabolized in PC synthesis and the glycerophospholipid metabolism pathway, and disturbance of the latter is associated with depression. Recent studies revealed that serum levels of PC (16:0/16) were elevated in antenatal depression and showed a positive trending correlation with depression scores [11][12][13]. Abundant evidence has uncovered psychological risk factors associated with PD, including depression and anxiety, and psychotherapy inter-ventions are considered effective in PD accordingly [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the present review reports moderate quality evidence that suggests KT may be effective on anxiety during dysmenorrhea. This is of significance as the presence of anxiety or related psychological stress in women relates to exacerbation of dysmenorrhea and vice versa [30,31]. Persistent pain could also result in development of stress, and related somatic symptom disorders in women with PD [32].…”
Section: Accepted Manuscriptmentioning
confidence: 99%